2015
DOI: 10.5505/tjtes.2015.74150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lateral deltoid splitting and deltopectoral approaches in the treatment of proximal humerus fractures

Abstract: ÖZET AMAÇ: Proksimal humerus kırıkları sık görülen ve fonksiyonel kısıtlanmaya neden olan kırıklardandır. Bu geriye dönük çalışmanın amacı aynı fiksasyon metodu kullanılarak deltopektoral ile deltoid split girişimin karşılaştırılmasıdır. GEREÇ VE YÖNTEM: BULGULAR:Lateral deltoid split girişim kullanılan olgularda baş ve tüberküler fragman redüksiyonunun daha iyi olduğu ve Constant omuz skorunun erken dönemde daha yüksek olduğu saptandı (sırasıyla, 66.8-57.4; p<0.01). Aksiller sinir gözlenip askıya alındığı iç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In contrast, an approach from the lateral side provides a convenient access to the displaced fragments and also for plate fixation on Section: Orthopaedics the lateral surface. [23] Many recent studies have shown excellent functional results with the lateral approach, whether extended or minimal, with no incidence of any axillary nerve palsy or any other significant complications. [14,24] In fact, most studies involving comparison of the functional results between the deltopectoral and deltoid splitting approaches have come out with better functional scores using the deltoid splitting approach.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, an approach from the lateral side provides a convenient access to the displaced fragments and also for plate fixation on Section: Orthopaedics the lateral surface. [23] Many recent studies have shown excellent functional results with the lateral approach, whether extended or minimal, with no incidence of any axillary nerve palsy or any other significant complications. [14,24] In fact, most studies involving comparison of the functional results between the deltopectoral and deltoid splitting approaches have come out with better functional scores using the deltoid splitting approach.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, an approach from the lateral side provides a convenient access to the displaced fragments and also for plate fixation on the lateral surface. 6 Many recent studies have shown excellent functional results with the lateral approach, whether extended or minimal, with no incidence of any axillary nerve palsy or any other significant complications. 7,15 In fact, most studies involving comparison of the functional results between the deltopectoral and deltoid splitting approaches have come out with better functional scores using the deltoid splitting approach.…”
Section: Discussionmentioning
confidence: 99%
“…The transdeltoid or the deltoid splitting approach obviates some of these disadvantages of the deltopectoral approach and provides convenient access to the lateral surface of the proximal humerus. 2,[5][6][7] But there have been concerns regarding the use of deltoid splitting approach due to the potential of injury to the axillary nerve that traverses around the surgical neck of humerus, through the substance of the deltoid; and also because of the fact that splitting the deltoid could result in weakening of this muscle and resultant difficulty in shoulder movements, particularly abduction.…”
Section: Introductionmentioning
confidence: 99%
“…4 The 2 most common open surgical approaches for greater tuberosity fractures are the deltopectoral approach or the directelateral deltoid-splitting approach. 5 Although considerable debate remains on the most optimal of these 2 approaches for more complicated fracture patterns, an all-arthroscopic technique has been employed for isolated, displaced greater tuberosity fractures. Multiple different techniques for fixation of greater tuberosity fractures have been reported, including screw fixation, single-and double-row anchor fixation, and bridging constructs.…”
mentioning
confidence: 99%